Prevalence of tobacco, alcohol and subtance use among undergraduate Boğaziçi University Students and exploration of specified risk factors - Taner, Sevil. (Thesis (M.A)-Bogazici University. Institute of Social Sciences, 2005., 2005)
Substance use is a phenomenon, which can be observed in different forms and displays all around the world. The transition to college which involves individual and contextual changes that can increase or enhance vulnerabilities might lead to substance use problems. The aim of this study was to find out the prevalence and onset of tobacco, alcohol and substance use among Boğaziçi University undergraduate students, and exploration of specified risk factors. The subjects of the study were comprised of 673 undergraduate B.U. students who were sampled by using a multistage cluster sampling method according to faculty and grade level. The sample constituted of 311 male (46.3%) and 361 female (57.3%) students. "Tobacco, alcohol and substance use prevalence questionnaire" which was developed by the researcher was administered during class hours. Alcohol was the most prevalent substance (66.5%) followed by tobacco (60.2%) and marijuana (9.2%). The prevalence of using any substance except from marijuana at least once in lifetime was 7%. Majority of the subjects started to use marijuana (86.9%) and ecstasy (80.3%) after university enrollment. Prevalence rates did not differ according to gender. Paternal and sibling's, best friends substance use, approval of use of substances and risk taking behavior were related positively while perceived harm and availability, importance of and attendance to religion, were found to be negatively related with prevalence rates. Despite limitations such as generalizability the findings of this study provide evidence that substance use was occurring among undergraduate B.U. students and that rates of using illegal drugs at least once in lifetime (9.2%) was higher compared to available Turkish youth data (6.7%).
Keywords: Teenagers -- Substance use.; Teenagers -- Tobacco use.; Teenagers -- Alcohol use.